Parasitic Intestinal Protists of Zoonotic Relevance Detected in Pigs by Metabarcoding and Real-Time PCR - Christen Rune Stensvold; Kateřina Jirků-Pomajbíková; Katrine Wegener Tams; Pikka Jokelainen; Rebecca P. K. D. Berg; Ellinor Marving; Randi Føns Petersen; Lee O’Brien Andersen; Øystein Angen; Henrik Vedel Nielsen (Microorganisms, 2021)
Several parasite species are shared between humans and pigs. We explored the application of next-generation sequencing-based metabarcoding supplemented with real-time PCR to fecal DNAs from 259 samples from 116 pigs in Denmark to detect and differentiate single-celled intestinal parasites of zoonotic relevance. Enterocytozoon bieneusi, Balantioides coli, and Giardia duodenalis were observed in 34/37 (92%), 148/259 (57%), and 86/259 (33%) samples, respectively. Entamoeba polecki ST1, E. polecki ST3, and Entamoeba hartmanni were detected in 104/259 (40%), 161/259 (62%), and 8/259 (3%) samples, respectively. Metabarcoding and real-time PCR detected Cryptosporidium in 90/259 (35%) and 239/259 (92%) of the samples, respectively, with Cryptosporidium suis and Cryptosporidium scrofarum observed in nearly equal proportions. Blastocystis subtypes 1, 3, 5, and 15 were found in 72 (28%), 6 (2%), 176 (68%), and 36 (14%) of 259 samples, respectively. Iodamoeba was identified in 1/259 samples (<1%), while none of 37 tested samples was positive for Dientamoeba fragilis. Our results illustrate how metabarcoding exemplifies a ‘one-fits-many’ approach to detecting intestinal single-celled parasites in feces supplemented with real-time PCR for selected parasites. Using metabarcoding with pathogen-specific assays may help detect emerging and previously underdetected pathogens and further elucidate the role of micro-eukaryotic parasites in human and animal health and disease.